Effects of dairy farm effluent compost on Growth and yield of pak choy (brassica rapa l.) In pot system - Andrea Joyce Maludin; Nur Aisar Izzati Che Musa; Jupikely James Silip; Yap Yun Fook; Januarius Gobilik (e-VIBS, Faculty of Science and Natural Resources, 2019)
Compost produced from dairy farm waste has been reported to be useful to increase and sustain crop yield. However, there is little known about this in Sabah. Thus, the present study was carried out to investigate the effects of locally produced dairy farm effluent compost (DEC) on the growth and yield of two Pak Choy varieties: Brassica rapa L. ‘Curly Dwarf Pak Choy’ (CDP) and ‘Shanghai Dwarf Pak Choy’ (SDP). Pot experiments (18L pot size) of 8 treatments were laid out in a completely randomized design; the treatments were four mixtures of DEC and infertile soil (0:100, 25:75, 50:50 and 100:0, % w/w) with or without addition of 6g of NPK 15:15:15 fertilizer. The media (DECM) was first used to grow the CDP for two cycles and then the SDP for another two cycles. At the end of each cycle (42 – 45 day), growth was measured as height (cm), leaf number, leaf area (cm2 ) and root (g) to shoot (g) ratio (R:S). Yield was measured as fresh and dry matter weights of CDP and SDP (g/plant). It was found that CDP grown on the media with DEC addition did not grow well during the first cycle, indicating the unreadiness of the DEC for a use. In subsequent cycles, there was a significant increase in height, leaf number, leaf area and fresh and dry matter weights of CDP and SDP grown on compost media compared to that on control media (100% soil). The data indicated that 25:75 DECM is satisfactory to increase the yield of CDP and SDP. The highest yield of CDP was 71g/plant (214g/pot), achieved at 50:50 DECM, but this was not significantly higher than that at 25:75 DECM. In fact, addition of DEC into the media beyond 25% did not significantly increase the yield of CDP. The highest yield of SDP was 47g/plant (141 g/pot) and this was achieved at 25:75 DECM. NPK fertilizer supplement to DECM had significant effect on the yield of SDP, but for CDP, the effect was limited only in 50:50 DECM, meaning at a first use, soil with addition of properly composted DEC does not necessarily need to be supplemented with NPK fertilizer to increase crop yield; however, to sustain the yield, NPK addition is necessary. Well composted DEC has a potential to be used as soil amendment for improving leafy vegetable production without the need of fertilizer application, during the first or second planting cycle.